Managing the risk of the community engagement project: SME managerial skills transfer project at UNISA - Louise van Scheers (Problems and Perspectives in Management, 2016)
The aims of this project are to manage the risk of a community engagement project, improve managerial of SME owners in the Tshwane community and promote CE scholarship engagement. CE opportunities as well as the high failure rate of SMEs motivated the lecturers of the Department Marketing and Retail to initiate training workshops in their community. This CE project SME skills transfer workshops aims to expand the involvement with the community and develop community engagement projects in addition also transfer managerial skills to SME owners in the community. Quantitative, exploratory research was used in the form of questionnaires with owners of SMEs participating in the workshops. The conducted research established that the most successful advertising medium is wall painting. With this community engagement project it had been reached 200 SMEs. It has been promoted CE scholarship engagement and manage the risk of this project. One of the secondary objectives was to manage the risk of this project. The results in table 1 indicate that the risk is managed adequately. This project is not considered as a high risk project for the university. The aims were achieved as evidence of transferring of managerial skills; managing risk of the project, promotion of CE scholarship and publishing articles through our CE project were achieved. Keywords: SME managerial skills transfer, risk management, community engagement, Tshwane community, advertising media, advertising key success factors, word of mouth. JEL Classification: M37